Makna Aktivitas Leksem Sapaan Orang dalam Bahasa Jawa Dialek Kemantren, Mojokerto: Analisis Kompenensial - Devita Septian Dwi Hidayati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to explore the definitive meanings of forms of address used by the community of Kemantren Village, Mojokerto, and to analyse the differences and similarities in the meanings of each lexeme of address using compositional analysis methods. This study uses data in the form of 16 lexemes of address obtained from researchers who are native speakers of Javanese. Data collection was conducted introspective based on the instincts of native speakers who had lived in the environment. The data was then corroborated through interviews with the researcher's mother and sister. The results of this study are 16 definitions of greeting lexemes in the Kemantren dialect of Mojokerto.